2014
DOI: 10.1016/j.matdes.2014.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of water hyacinth fibers – polyester composites before and after immersion in water

Abstract: This study reported moisture absorption of untreated and treated individual water hyacinth (WH) fibers as well as comparison the mechanical properties of WH fibersunsaturated polyester (UPR) matrix composites after and before immersion in water. The result shows that the individual WH fibers treated with various alkali concentration did not exhibit significantly decreases of their moisture absorption. SEM photograph in cross section of the treated WH fibers shows swollen cell wall containing more nano and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 18 publications
3
48
0
4
Order By: Relevance
“…The peaks at 1346 cm −1 and 1500 cm −1 were disappeared in the microwave treated sample, indicating that lignin was removed. This is in agreement with Abral, 2014 [19] and Sundari, 2012 [20]. These observations indicate that microwave treatment removed lignin leading to expelling of cellulose and hemicellulose from tight matrices.…”
Section: E Effect Of Temperature On Reducing Sugar and Lignocellulossupporting
confidence: 91%
See 1 more Smart Citation
“…The peaks at 1346 cm −1 and 1500 cm −1 were disappeared in the microwave treated sample, indicating that lignin was removed. This is in agreement with Abral, 2014 [19] and Sundari, 2012 [20]. These observations indicate that microwave treatment removed lignin leading to expelling of cellulose and hemicellulose from tight matrices.…”
Section: E Effect Of Temperature On Reducing Sugar and Lignocellulossupporting
confidence: 91%
“…5 shows FTIR spectra of the untreated water hyacinth and the treated samples. The peaks were observed at 1240 and 1346 cm −1 are those of C−O stretching of syringyl lignin and C−O−C of hemicellulose oscillation in anomeric region [19]. The peak at 1500 cm −1 indicates the CC stretching of aromatic rings of lignin [20].…”
Section: E Effect Of Temperature On Reducing Sugar and Lignocellulosmentioning
confidence: 99%
“…H. Abral et al reported the effects of moisture absorption for untreated and treated water hyacinth fibres. They observed that alkaline treatment did not significantly reduce the moisture absorption [23].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that some the fibers was not glued effectively by the matrix, and not dispersed homogeneously in the matrix [11,12]. Because of high volume content of fibers, agglomeration is possible to exist in the composite matrix.…”
Section: Introductionmentioning
confidence: 99%